Амфори із сільських некрополів Ольвійського полісу VI–III ст. до н. е.: центри виробництва, сакрально-ритуальний аспект - Снитко, І.О. (Археологія, 2016)
У контексті з символікою поховального культу розглядається найбільш поширена категорія знахідок серед поховальних комплексів античних некрополів Нижнього Побужжя. In the article presented, analysed are the amphorae, the most mass category of the findings in graves of the burial grounds at Olbian chora. Amphorae were used mainly as the funeral property, and also for the libations during the funeral procedure and the following funeral feast in the Archaic and the Early Classical periods. Used were mainly the vessels from the Greek centres leading the most intensive trade with Olbia, among which Chios, Samos, Attic, Klazomenai, and Lesbos prevailed. In the Late Classical period, besides their usage in the burial inventory structure and for funeral rites, amphorae were widely used as the details for funeral structures building: cromlechs, vertical slabs covering the entrance into an undercut grave. The most often used for these purposes were the amphorae of Chios, Herakleia Pontike, and Thasos. It can be stated that amphorae were one of the most important elements in funeral rites for the Olbian polis population during the period from the 6th to the 3rd centuries BC. В предлагаемой статье рассматривается наиболее массовая категория находок в погребениях могильников хоры Ольвии — амфоры. В позднеархаическую—раннеклассическую эпохи амфоры использовались преимущественно в качестве погребального реквизита, а также для возлияний при проведении похоронной процедуры и последующей тризны. В основном использовалась тара ведущих наиболее интенсивную торговлю с Ольвией греческих центров, среди которых преобладали Хиос, Самос, Аттика, Клазомены, Лесбос. В позднеклассическую эпоху, кроме использования в составе погребального инвентаря и для проведения ритуально-поминальной церемонии, амфоры широко применяются и в качестве деталей для обустройства погребальных сооружений (кромлехи, заклады подбоев). Наиболее применимыми в этих целях были амфоры Хиоса, Гераклеи Понтийской и Фасоса. Можно констатировать, что для населения Ольвийского полиса амфорная тара являлась одним из главных элементов при проведении погребальной процедуры в VI—III вв. до н. э.